A rediscovered low-land Tofan variety - Ragagnin Elisabetta (2009)
The eastern territories of Kubsugul province in northern Mongolia, i.e. east of Lake Kubsugul, are home to a small group of Sayan Turkic speakers. Their self-designation is tuha, a phonetic variant of tuva/tuba. In the available literature they are referred to as Uyghur Uriankhay. The present paper will present a first overview of this remarkable Sayan variety, focusing on its lexical, phonetic and morphological features. It will be shown that, on the one hand, Tuhan shows peculiarities that distinguish it from the rest of Sayan Turkic and that, on the other hand, it shares some salient isoglosses with Tofan. It will be argued that Tuhan represents a lowland or steppe variety as opposed to the taiga or highland variety of Tofan.